Preliminary findings on the effect of childhood trauma on the functional connectivity of the anterior cingulate cortex subregions in major depressive disorder - Rong, Bei; Gao, Guoqing; Sun, Limin; Zhou, Mingzhe; Zhao, Haomian; Huang, Junhua; Wang, Hanling; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2023)
Childhood trauma (CT) is a known risk factor for major depressive disorder (MDD), but the mechanisms linking CT and MDD remain unknown. The purpose of this study was to examine the influence of CT and depression diagnosis on the subregions of anterior cingulate cortex (ACC) in MDD patients. The functional connectivity (FC) of ACC subregions were evaluated in 60 first-episode drug-naïve MDD patients (40 with moderate-to-severe and 20 with no or low CT), and 78 HC (19 with moderate-to-severe and 59 with no or low CT). The correlations between anomalous FC of ACC subregions and the severity of depressive symptoms and CT were investigated. Individuals with moderate-to-severe CT exhibited increased FC between the caudal ACC and the Middle frontal gyrus (MFG) than individuals with no or low CT, regardless of MDD diagnosis. MDD patients showed lower FC between the dorsal ACC and the Superior frontal gyrus (SFG) and MFG, between the subgenual/perigenual ACC and the middle temporal gyrus (MTG) and angular gyrus (ANG) than HC, regardless of CT severity. The FC between left caudal ACC and left MFG mediated the correlation between CTQ and HAMD-cognitive in MDD patients. Our findings demonstrated that functional changes of caudal ACC mediated the correlation between CT and MDD. The results of these studies contribute to our understanding of the neuroimaging mechanisms of CT and MDD.